Population Modeling of Selexipag Pharmacokinetics and Clinical Response Parameters in Patients With Pulmonary Arterial Hypertension. (27th May 2017) - Krause, A; Machacek, M; Lott, D; Hurst, N; Bruderer, S; Dingemanse, J
Abstract : Selexipag (Uptravi) is an oral selective IP prostacyclin receptor agonist approved for the treatment of pulmonary arterial hypertension (PAH). The pivotal GRIPHON study was the largest clinical study ever conducted in PAH patients, providing long‐term data from 1, 156 patients. PAH comedication did not affect exposure to selexipag, while exposure to its active metabolite ACT‐333679 was reduced by 30% when taken in combination, clinically not relevant in the context of individual dose up‐titration. Using log‐linear regression models linking model‐predicted steady‐state exposure to pharmacodynamics (PD), exposure to selexipag and ACT‐333679 showed some statistically significant, albeit not clinically relevant, effects on exercise capacity, laboratory values, and the occurrence of prostacyclin‐related adverse events, but not on vital signs or adverse events denoting hemorrhage. Using suitable modeling techniques, the GRIPHON study yielded clinically relevant data with limited burden of pharmacokinetics (PK) blood sampling, demonstrating that PK/PD modeling enables firm conclusions even with sparse PK and PD sampling.